Galactosyltransferase GhRFS6 interacting with GhOPR9 involved in defense against Verticillium wilt in cotton. (March 2023) - Chang, Baiyang; Zhao, Lihong; Feng, Zili; Wei, Feng; Zhang, Yalin; Zhang, Yihao; Huo, Peng; Cheng, Yong; Zhou, Jinglong; Feng, Hongjie
Abstract: The soil-borne fungus Verticillium dahliae causes Verticillium wilt (VW), one of the most devastating diseases of cotton. In a previous study showed that GhOPR9 played a positive role in resistance of cotton to VW through the regulation of the Jasmonic acid (JA) pathway. Furtherly, we also found that GhOPR9 interacted with a sucrose galactosyltransferase GhRFS6. Raffinose synthase ( RFS ) plays a key role in plant innate immunity, including the abiotic stress of drought, darkness. However, there were few reports on the effects of RFS on biotic stress. In this study, we verified the function of GhRFS6 to VW. The expression analysis showed that the GhRFS6 may be regulated by various stresses, and it was upregulated under Vd076 and Vd991 pressures. Inhibition of GhRFS6 expression, hydrogen peroxide (H2 O2 ) content, lignin content, cell wall thickness and a series of defense responses were decreased, and the resistance of cotton to V. dahliae was decreased. In addition, this study showed that GhRFS6 has glycosyltransferase activity and can participate in the regulation of α-galactosidase activity and raffinose and inositol synthesis. And that galactose was accumulated in cotton roots after GhRFS6 silencing, which is beneficial for the colonization and growth of V. dahliae . Furthermore, overexpression of GhRFS6 in Arabidopsis thaliana enhanced plant resistance to V. dahliae . In GUS staining, the promoter expression position of GhRFS6 was also altered after V. dahliae infection. Meanwhile, GhRFS6 has also been shown to resist VW through the regulation of the JA pathway. These results suggest that GhRFS6 is a potential molecular target for improving cotton resistance to VW. Highlights: GhRFS6 was involved in cotton against Verticillium wilt by interacting with the disease resistance protein GhOPR9. GhRFS6 was involved in the synthesis of jasmonic acid. GhRFS6 was involved in the resistance to V. dahliae through the sugar metabolism pathway. GhRFS6 affects the synthesis of plant cell wall by regulating the content of pectin.